2005
DOI: 10.1177/107110070502600202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hallux Valgus Surgical Outcome With AOFAS Forefoot Score and Radiological Parameters

Abstract: Patients who had hallux valgus surgery had significant improvements in four of their SF-36 scores, four of five of AAOS lower extremity scores, and AOFAS scores. The degree of deformity, amount of correction, or type of operation did not influence outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0
20

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 6 publications
8
99
0
20
Order By: Relevance
“…It was not surprising that the AOFAS scale did not reflect the outcome of hallux valgus surgery properly [22]. Radiological parameters should always be assessed to encompass all aspects.…”
Section: Discussionmentioning
confidence: 99%
“…It was not surprising that the AOFAS scale did not reflect the outcome of hallux valgus surgery properly [22]. Radiological parameters should always be assessed to encompass all aspects.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that although being overweight brings a greater chance of tendinitis, plantar fasciitis and osteoarthritis, normal-weight patients are more likely to develop HV. Conversely, Cho et al reported that patients with higher BMI are more prone to develop HV [13]. In 2010, the MOBILIZE Boston Study reported that the prevalence of HV in women decreases with increased BMI [18].…”
Section: Discussionmentioning
confidence: 99%
“…It comprises three sections related to pain, function and alignment assessment, with the worst score being 0 and the best 100. Worth noting is the proven correlation of AOFAS-HMI score with radiological results obtained after surgical correction of HV was described [13]. VAS was used to evaluate pain, where 0 is no pain and 10 is the worst pain possible.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the most critical variable to post-operative satisfaction in women was "the appearance of their foot" and that this was closely related to the "range of shoes that they were able to wear". Thordarson et al [17] (2005) described that "postoperatively, most patients resumed fashionable or conventional shoes without an insert". However, appraisal of their results showed that, despite overall improvement in the AAOS Foot and Ankle Core score, the standardized Shoe Comfort score remained 58.7 out of 100 at 24 mo follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are typically counselled to anticipate a period of post-operative swelling and discomfort proportional to the required degree of correction and the amount of soft tissue disruption. Previous reports suggest that patients should expect to return to comfortable footwear between 6 wk and 6 mo post-operatively, depending on operative and patient factors [6,7,11,17] . However, the evidence documenting footwear outcomes following hallux valgus surgery is limited.…”
Section: Introductionmentioning
confidence: 99%